THE INFLUENCE OF POLITICAL CONNECTION, OWNERSHIP STRUCTURE AND CASH HOLDINGS ON CORPORATE PERFORMANCE IN NONFINANCIAL COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE - Prastiono Prastiono; Sinta Arimamukti (JURNAL STUDI MANAJEMEN ORGANISASI, 2019)
As there inconsistencies from previous research about political conection toward corporate performance, wether improve nor decrease. Furthermore ownership structure and cash holding do not always give positive impact on corporate performance.This research aims to analyze the influence of  political connection, ownership structure, and cash holdings on corporate performance in nonfinancial companies listed on the Indonesian Stock Exchange.The population of this research are nonfinancial companies listed on the Indonesian Stock Exchange period 2013-2016. The data sorted using purpose sampling method. The analytical tool used is panel data regression.The result of this research shows that political connection, institutional ownership, and cash holdings have significant positive effect on corporate performance. On the other hand foreign ownership have significant negative effect on corporate performance.